Finite Element Analysis of an Unsteady MHD Normal Convection Flow of a Casson Fluid Past a Vertical Oscillating Plate in Porous Medium with Effect of Heat Source and Eckert Number - Kune, Ramesh; Naik, S. Hari Singh (Communications in Mathematics and Applications, 2023)
An investigation of unsteady MHD free convection flow over a changeable permeable plate with Casson fluid in the presence of heat absorption and Eckert number effects have been carried out. The governing equations of the flow are solved by Galerikin method. Velocity, temperature and concentration profiles are analyzed through the graphs with effects of Casson, permeability, phase angle, Eckert number and chemical reaction parameter, which provide excellent correlation with the previous results.